« Faire intimité » en migration - Audran Aulanier; Laura Odasso (Sociologies)
Drawing on a literature review of diverse conceptions of intimacy in migration, this introduction underscores that intimacy, while inherently tied to a sense of interiority, is shaped by social norms, institutional directives and relational dynamics. As such, intimacy serves as an analytical lens for exploring the process of subjectivation and their room of manoeuvre within migratory regimes – shedding light on how migrants “do intimacy”. The aim of the special issue, as outlined in this introduction, is to examine the plurality of attachment forms and identity reconfigurations within migrants’ intimate spheres. In doing so, it strikes the delicate balance between exposing the oppressions experienced in migration and emphasising the everyday possibilities of forging intimate spaces.